2018
DOI: 10.1139/cgj-2017-0155
|View full text |Cite
|
Sign up to set email alerts
|

Field study on axial bearing capacity and load transfer characteristic of waveform micropile

Abstract: The waveform micropile is an advanced construction method that combines the concept of the conventional micropile with the jet grouting method. This new form of micropile was developed to improve shaft resistance, and has enabled a higher bearing capacity and greater cost efficiency. Two field tests were conducted to examine field applicability and to verify the effects of bearing capacity enhancement. In particular, waveform micropile construction using the jet grouting method was performed to evaluate the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
(13 reference statements)
2
13
0
1
Order By: Relevance
“…This finding indicates that shear keys along the pile increased its shaft resistance. This effect was more significant in the soil region with a higher confining pressure, which is in good agreement with the results of Jang and Han [36,37]. Interestingly, WMP2 provided a similar shaft resistance to CMP1 despite being only about 80% of its length.…”
Section: Axial Load Transfer Mechanism In Micropilessupporting
confidence: 90%
See 1 more Smart Citation
“…This finding indicates that shear keys along the pile increased its shaft resistance. This effect was more significant in the soil region with a higher confining pressure, which is in good agreement with the results of Jang and Han [36,37]. Interestingly, WMP2 provided a similar shaft resistance to CMP1 despite being only about 80% of its length.…”
Section: Axial Load Transfer Mechanism In Micropilessupporting
confidence: 90%
“…The piles' lengths, L, are related by the scale factor N. The effects of the piles' form and length, and consequently their axial stiffness, were evaluated by comparing two types of conventional micropile (CMP) and two types of waveform micropile (WMP) in foundation underpinning tests. The WMP (Figure 2a), with shear keys along the pile shaft, demonstrated a higher stiffness and load bearing capacity than the CMP [35][36][37]. Although the limitation of the soil stress effect in small-scale tests is difficult to overcome, to establish a reliable relation between the small-scale model and the prototype model requires adopting a suitable scale and satisfying the scaling law [38,39].…”
Section: Test Apparatusmentioning
confidence: 99%
“…The high-strength steel rebar transfers the load to the surrounding ground through the grout body to develop frictional resistance. Therefore, the micropile supports the load via the shaft resistance created between the pile shaft and the ground while the load carrying capacity resulting from tip resistance is generally neglected due to small diameter of the micropile [15]. Federal Highway Administration (FHWA) micropile design guidelines specify the bond strength (a bond ) considering the frictional resistance between the grout and the ground for micropile design [10].…”
Section: Introductionmentioning
confidence: 99%
“…In previous research studies, the constructability and the increased bearing capacity of the waveform micropile were verified through both field tests and field applications. In addition, the test results showed that the waveform micropile is an effective method for reducing construction time with simplified construction steps relative to the conventional micropile [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the WMP does not require casings during drilling, and therefore, can facilitate a faster installation process and cost effectiveness (Drbe and El Naggar, 2014;Abdlrahem and El Naggar, 2019). During its construction, jetgrouting methods are used to develop shear keys along the pile shafts by controlling the grouting pressure and ascent time (Jang and Han, 2018). Figure 1 depicts the construction process of an instrumented WMP: (a) drilling a hole through a water jet; (b) waveform grout formation by controlling grouting pressure and time; (c) inserting reinforcing steel bar; (d) grout curing for a month.…”
Section: Introductionmentioning
confidence: 99%